Automatic glass-slide capturing system for cervical cancer pre-screening program - Nor Rizuan, Mat Noor; Nor Ashidi, Mat Isa; Mohd Yusoff, Mashor; Kamal Zuhairi, Zamli; Mohammad Subhi Al-Batah (Science Publications, 2009)
Link to publisher's homepage at http://scipub.org/scipub/c4p.php?j_id=ajas